Pulmonary Artery Banding for Ventricular Rehabilitation in Infants With Dilated Cardiomyopathy: Early Results in a Single-Center Experience - Di Candia, Angela; Castaldi, Biagio; Bordin, Giulia; Cerutti, Alessia; Reffo, Elena; Biffanti, Roberta; Di Salvo, Giovanni; Vida, Vladimiro L.; Padalino, Massimo A. (Frontiers in Pediatrics, 2020)
Background Pulmonary artery banding (PAB) is reported as an innovative strategy for children with end stage heart failure (ESHF) to bridge to transplantation or recovery. We report our early experience with PAB to evaluate outcomes, indications and limitations. Materials and methods. This is a single center prospective clinical study, including infants and children admitted for ESHF due to dilative cardiomyopathy (DCM) with preserved right ventricular function, after failure of maximal conventional therapy. All patients underwent perioperative anti-congestive medical therapy with ACE inhibitor, beta blocker and spironolactone. Postoperatively, all patients underwent echocardiographic follow up to assess myocardial recovery. Results We selected 5 patients (4 males) who underwent PAB at a median age of 8.6 months (range 3.9-42.2 months), with preoperative ejection fraction (EF) < 30%. Sternal closure was delayed in all. One patient did not improve after PAB, and underwent Berlin Heart implantation after 33 days, followed by heart transplant after 13 months. 4 patients were discharged home on full anticongestive therapy. However, 2 months after discharge, 1 patient experienced severe acute heart failure secondary to pneumonia, which required mechanical cardiac support, and underwent a successful heart transplant after 21 days. The remaining 3 patients are doing well at home, 22.4, 16.9 and 15.4 months after PAB. They all underwent elective percutaneous de-banding, 18.5, 4.8 and 10.7 months after PAB). Ejection fraction increased from 17.7 ±8.5% to 63.3±7.6% (p=0.03), and they have all been delisted. Conclusion Use of PAB may be an effective alternative to mechanical support in selected infants for bridging to transplant or recovery. Better results seem to occur in patients age < 12 months. Further experience and research are required to identify responders and non-responders to this approach.